2014
DOI: 10.1002/adem.201400358
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Bimodal Structure Topology in the Control of Mechanical Properties of a Stainless Steel

Abstract: Refinement of microstructure from ordinary coarsegrained (CG; grain size d ! 10 mm) down to ultrafine-grained (UFG; grain size d 1 mm), and even further to nano-scale, is a well-proven approach for the strengthening of metallic materials. [1][2][3] However, the downside of bulk UFG metals is their rather poor ductility resulting from very limited capacity for dislocation storage and therefore early strain localization during mechanical loading. [2][3][4][5] Since both strength and ductility are important chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…7,11,15) Hence, the controlled mechanical milling via the jet mill proved extremely effective in achieving controlled severe plastic deformation, limited to the sub-surface regions of the fine size powder particles, in the form of a featureless "shell" region. As a result, jet milling successfully created a bimodal microstructure in the milled powder particles, i.e.…”
Section: Microstructural Evolution During Jet Milling Processmentioning
confidence: 99%
“…7,11,15) Hence, the controlled mechanical milling via the jet mill proved extremely effective in achieving controlled severe plastic deformation, limited to the sub-surface regions of the fine size powder particles, in the form of a featureless "shell" region. As a result, jet milling successfully created a bimodal microstructure in the milled powder particles, i.e.…”
Section: Microstructural Evolution During Jet Milling Processmentioning
confidence: 99%
“…Recently, Ameyama and co-workers have proposed a microstructural design to improve mechanical properties by obtaining both high strength and high ductility in metallic materials, through the formation of so-called harmonic structured material [1][2][3][4][5][6][7][8][9][10][11][12][13] . Essentially, it is an exquisite heterogeneous microstructural design, consisting of bimodal grain size distribution, in which ductile coarse grained regions (termed as core ) are enclosed in a continuously connected three-dimensional networks regions with high strength ultra-ne grained structure, known as shell .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other important observations were also made from these studies: (a) Both random and HS bimodal exhibit same strength but HS exhibit higher ductility when compared to random bimodal; (b) the HS specimens show extremely small variation of properties when compared to random bimodal specimens. [19,24,25] Moreover, in general, it was also observed that the harmonic structure design promotes uniformity of deformation when compared to random bimodal structure, leading to suppressed strain localization and relatively higher tensile ductility.…”
mentioning
confidence: 99%
“…The effect of topological distribution of fine-and coarse areas on the properties was also evaluated wherein random bimodal was created by mixing severely milled powders with un-milled initial powders. [19,24,25] It was observed that the random bimodal structured specimens demonstrated higher strengths when compared to bulk CG specimens. Moreover, other important observations were also made from these studies: (a) Both random and HS bimodal exhibit same strength but HS exhibit higher ductility when compared to random bimodal; (b) the HS specimens show extremely small variation of properties when compared to random bimodal specimens.…”
mentioning
confidence: 99%
See 1 more Smart Citation